Multicomponent physical fitness evaluation as a developmental baseline for youth athletes in jakarta’s long-term water ski and wakeboard training program - Uzizatun Maslikah; Fahmy Fachrezzy; Iwan Hermawan; Mansur Jauhari; Viranti Citrasari; Arga Nurcahya (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
The scientific profiling of youth athletes in water ski and wakeboard sports remains limited, particularly in Southeast Asia, where empirical baseline data to support Long-Term Athlete Development (LTAD) frameworks are scarce. Although structured training programs have been implemented in Jakarta, no published research has comprehensively evaluated the multicomponent physical fitness characteristics of Indonesian youth athletes in these disciplines. Therefore, this study aimed to provide a descriptive–evaluative baseline analysis of physical condition profiles to inform long-term athlete development planning. A descriptive quantitative cross-sectional design was employed involving 24 male and female athletes (aged 13–18 years) selected through purposive sampling from Jakarta’s official 2025 long-term training cohort. A standardized multicomponent fitness battery was administered, including the Yo-Yo Intermittent Recovery Test Level 1 (aerobic endurance), 30-second Wingate Anaerobic Test (anaerobic capacity), 1RM strength testing, Standing Broad Jump (power), Illinois Agility Test, coordination and balance assessments, and Sit-and-Reach flexibility testing. Data were analyzed using descriptive statistics, independent-sample t-tests, and one-way ANOVA with effect size calculations (p < 0.05). Results indicated moderate-to-good aerobic endurance (1,560 ± 210 m), good anaerobic peak power (10.8 ± 1.3 W·kg⁻¹), above-average muscular strength (34.5 ± 4.2 kg), good lower-limb power (205.4 ± 15.8 cm), good agility (17.2 ± 0.9 s), above-average flexibility (32.6 ± 5.1 cm), and strong balance performance (42.3 ± 8.6 s). Aerobic endurance showed the greatest variability, while anaerobic power and agility emerged as dominant characteristics. These findings establish the first integrated physical fitness baseline for Indonesian youth water ski and wakeboard athletes and provide practical guidance for individualized LTAD-based conditioning programs.